(untitled) (Педагогіка вищої та середньої школи, 2008)
The article deals with the research of communicative competence development peculiarities of the students of higher educational establishments. The paper describes 6 stages of training activity of the students based on the support materials as a means of educational and pedagogic purposes of training practice reaching.